A novel homozygous mutation in LSS gene possibly causes hypotrichosis simplex in two siblings of a Tibetan family from the western Sichuan province of China - Zhao, Bei; Tang, Yisi; Chen, Wenjing; Wan, Huiying; Yang, Jiyun; Chen, Xuejun (Frontiers in Physiology, 2023)
Aim: Hypotrichosis simplex (MIM 146520) is a rare form of monogenic hereditary alopecia. Several genes including LPAR6, LIPH and DSG4 associated with the disease have been identified. LSS encoding Lanosterol synthase (LSS) has been shown to cause hypotrichosis simplex but the related mechanisms remain elucidated. This study aims to find mutations in LSS from a Chinese family, among which a 21-years-old male patient and his 9-years-old sister suffer from hypotrichosis simplex. Methods: Dermoscopy and histological analysis were used to examine patients’ scalps while the exome sequencing was used to find the mutations in LSS. Results: The hair loss was only detected on scalp of the proband and his sister while other ectodermal structures were normal with no systemic abnormalities. Further, the exome sequencing identified a new homozygous mutation NM_002340.6(LSS_v001):c.812T>C (p.(Ile271Thr)) in LSS gene of the proband, which was also found in his sister. In addition, heterozygous mutation of LSS was found in their asymptomatic parents. Finally, the possible protein structure of the mutational LSS was predicted. Conclusions: The hypotrichosis simplex reported here could be an autosomal recessive disease in this family. The mutation on LSS might reduce enzyme activity of LSS thus leading to the disease.